Brand Image and Consumer Perceived Values on Purchase Intention of Organic Food: A Conceptual Study - DingGe, Ji; Hee, Ong Choon (Business and Economic Research, 2024)
Organic food is quickly developing in China as consumer wealth and consumption levels have grown in recent years; the Chinese government's "Healthy China Action (2019-2030)" promotes a balanced diet and works to raise the standard of agricultural output and food safety. Even though China has Asia's largest organic food market, organic food has a small market share and low consumer expenditure. As a result, decisive steps to boost the growth of China's organic food market are urgently needed. This study aims to explore the factors related to Chinese people’s purchase intention of organic food using the S-O-R model. Brand image and consumer perceived values are crucial because they influence customer purchase behavior. This study emphasizes brand image, perceived functional, emotional and social values on consumer purchase intention. Epistemic value and conditional value were excluded because they have detrimental impacts on consumer choice behavior. The contribution of this study is to enrich the existing literature by providing a deeper understanding of organic food consumer purchase intention in China through the application of brand image and consumer perceived values using the S-O-R model. It also provides Chinese policymakers and organic food suppliers with solutions to increase organic food sales to expand the Chinese organic food market.